Exploring the Metabolic Stability of Engineered Hairy Roots after 16 Years Maintenance - Häkkinen, Suvi T.; Moyano, Elisabeth; Cusidó, Rosa M.; Oksman-Caldentey, Kirsi-Marja (Frontiers in Plant Science, 2016)
Plants remain a major source of new drugs, leads and fine chemicals. Cell cultures deriving from plants offer a fascinating tool to study plant metabolic pathways and offer large scale production systems for valuable compounds – commercial examples include compounds such as paclitaxel. The major constraint with undifferentiated cell cultures is that they are generally considered to be genetically unstable and cultured cells tend to produce low yields of secondary metabolites especially over time. Hairy roots, a tumour tissue caused by infection of Agrobacterium rhizogenes is a relevant alternative for plant secondary metabolite production for being fast growing, able to grow without phytohormones, and displaying higher stability than undifferentiated cells. Although genetic and metabolic stability has often been connected to transgenic hairy roots, there are only few reports on how a very long-term subculturing effects on the production capacity of hairy roots. In this study, hairy roots producing high tropane alkaloid levels were subjected to 16 -year follow-up in relation to genetic and metabolic stability. Cryopreservation method for hairy roots of H. muticus was developed to replace laborious subculturing, and although the post-thaw recovery rates remained low, the expression of transgene remained unaltered in cryopreserved roots. It was shown that although displaying some fluctuation in the metabolite yields, even an exceedingly long-term subculturing was successfully applied without significant loss of metabolic activity.